Evaluating the underlying physiological and molecular mechanisms in the system of rice intensification performance with Trichoderma-rice plant symbiosis as a model system - Doni, Febri; Safitri, Ratu; Suhaimi, Nurul Shamsinah Mohd; Miranti, Mia; Rossiana, Nia; Mispan, Muhamad Shakirin; Anhar, Azwir; Uphoff, Norman (Frontiers in Plant Science, 2023)
The system of rice intensification (SRI) is an extensively-researched and increasingly widely-utilized methodology for alleviating current constraints on rice production. Many studies have shown physiological and morphological improvements in rice plants induced by SRI management practices to be very similar to those that are associated with the presence of beneficial microbial endophytes in or around rice plants, especially their roots. With SRI methods, grain yields are increased by 25-100% compared to conventional methods, and the resulting plant phenotypes are better able to cope with biotic and abiotic stresses. SRI management practices have been shown to be associated with significant increases in the populations of certain microorganisms known to enhance soil health and plant growth, e.g., Azospirillum, Trichoderma, Glomus, and Pseudomonas. This article evaluates the effects of applying Trichoderma as a model microbe for assessing microbial growth-promotion, biological control activity, and modulation of gene expression under the conditions created by SRI practices. Information about the molecular changes and interactions associated with certain effects of SRI management suggests that these practices are enhancing rice plants' expression of their genetic potentials. More systematic studies that assess the effects of SRI methods respectively and collectively, compared with standard rice production methods, are needed to develop a more encompassing understanding of how SRI modifications of crops’ growing environment elicit and contribute to more robust and more productive phenotypes of rice.